Counter-Narrative or Marketing Gimmick? Defining Male Beauty in Indonesian Skincare Ads from the Lens of Young Male Audience - Salsabila Mutia Rahmadani; Mashita Phitaloka Fandia Purwaningtyas (Masculinities and Social Change)
This paper originates from an awareness of a prevailing issue among Indonesian male audiences who tend to criticize the portrayals of male skincare users as deviating from traditional masculinity. Challenging these conventional ideals, MS Glow X Keanu ads features Indonesian male influencer, Keanu, who defies traditional male beauty notions by presenting traditionally feminine visual elements and practices that contradicts the established standards of male beauty advertising. This paper aims to provide insights into the perspective of young male audiences who are active skincare users as informants; how they define male beauty through the depiction of Keanu in the ads. Using a reception analysis method, this paper considers informants’ level of involvement in skincare usage and the influence of other internal and external socio-cultural factors on their interpretations. The findings show that even though informants tend to see and agree that Keanu’s appearance on the ads as the counter-narrative for stereotypical male beauty, they also suspect that Keanu’s usage as model of ads is merely a marketing gimmick from MS Glow, because of his virality and impact factors among Indonesian youngsters.